CD40 gene polymorphism and its expression in children with Kawasaki disease from North India: a preliminary case–control study and meta-analysis - Patra, Pratap Kumar; Jindal, Ankur Kumar; Rikhi, Rashmi; Kaur, Anit; Srivastava, Priyanka; Suri, Deepti; Rawat, Amit; Pilania, Rakesh; Singh, Surjit (Frontiers in Pediatrics, 2023)
Introduction. CD40 gene single nucleotide polymorphisms (SNPs) have been associated with susceptibility and development of coronary artery abnormalities (CAAs) in children with Kawasaki disease (KD) in Japanese, Chinese and Taiwanese populations. However, there is no data on SNPs in CD40 gene in patients with KD from Indian subcontinent. We studied the CD40 gene polymorphisms, and CD40 expression in children with KD from North India.Methods: SNPs in CD40 gene (rs4810485, rs1535045) were studied using Sanger sequencing. CD40 expression was studied flow cytometry. Metanalysis was carried out to assess the role of both SNPs of CD40 gene in KD. GRADEpro GDT software (v.3.2) was used to assess 'certainty of evidence'.Results: Forty-one patients with KD and 41 age, sex-matched febrile controls were enrolled.However, none of the alleles and genotypes of CD40 gene were found to be associated with KD. CD40 expression was higher in KD, and in KD with CAAs, as compared to controls but failed to reach statistical significance. In meta-analysis, T allele of rs153045 was found to be significantly associated with KD (OR=1.28; 95% CI:1.09-1.50; p=0.002). The GRADE of evidence for this outcome, however, is of ' very low certainty'.In the present study, there was no association of SNPs (rs4810485 and rs153045) with susceptibility to KD. This could be a reflection of a modest sample size. CD40 expression was higher in KD and in KD with CAAs. In metanalysis T allele of rs153045 was significantly associated with KD. Our study confirms that there is a significant genetic heterogeneity in KD among different ethnicities.